2008
DOI: 10.1002/app.28463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of swelling pretreatment on the deposition structure on electroless copper of polyacrylonitrile nanocomposites for electromagnetic interference shielding

Abstract: In this investigation, the electroless copper method with various cupric sulfate concentrations (0.24, 0.36, 0.48, 0.60M) without sensitizing and activating is used to deposit electroless copper compounds (CuS) on the swelling pretreatment polyacrylonitrile(SPAN) surface for electromagnetic interference (EMI) shielding materials. The acetic acid can swell polyacrylonitrile (PAN) effectively which donot destroy the hexagonal structure of polyacrylonitrile, only looses the molecule chain of polyacrylonitrile the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…A compact and uniform copper sulfide layer was successfully covered on the surface of PAN fibers as shown in Figure (b), which may be due to the a strong affinity for Cu 2+ ions provided by nitrile groups from PAN fibers and EDTA 2– . As reported before, it is believed that a continuous conducting layer could only be formed if there was a strong adhesive effect between the fiber matrix and the conductive phase . After ultrasonic washing in water for 30 min, the surface feature of copper sulfide‐coated PAN fibers [Figure (c)] remained intact, verifying the strong adhesion between the copper sulfide layer and PAN fibers.…”
Section: Resultssupporting
confidence: 64%
“…A compact and uniform copper sulfide layer was successfully covered on the surface of PAN fibers as shown in Figure (b), which may be due to the a strong affinity for Cu 2+ ions provided by nitrile groups from PAN fibers and EDTA 2– . As reported before, it is believed that a continuous conducting layer could only be formed if there was a strong adhesive effect between the fiber matrix and the conductive phase . After ultrasonic washing in water for 30 min, the surface feature of copper sulfide‐coated PAN fibers [Figure (c)] remained intact, verifying the strong adhesion between the copper sulfide layer and PAN fibers.…”
Section: Resultssupporting
confidence: 64%
“…The Cu x S containing materials prepared in this study exhibit higher EMI SE per unit surface density compared to other copper sulfide containing materials in the range of 500–3000 MHz ( Table 2 ). Some researchers reported electroless copper sulfide deposition on PAN thin‐film substrates to produce CuS/(S)PAN composites . Owing to this electroplating method, the distribution of copper sulfide is very uniform and therefore stable EMI shielding is found.…”
Section: Resultsmentioning
confidence: 99%
“…To improve the wear and water stability of the shielding material, crosslinking polyacrylonitrile nanofiber/metal nanoparticle hybrid membranes, antibacterial cotton fabrics, and super hydrophobic foams have been successfully developed. In addition, research revealed copper sulfide (Cu x S) possesses excellent conductivity and plays an important role in preparation of electromagnetic shielding materials . Thin PET fabrics coated with the Cu x S nanoparticles exhibited excellent conductivity and electromagnetic shielding properties .…”
Section: Introductionmentioning
confidence: 99%
“…It must be processed for the metallization and conductive treatment in order to have the function of electromagnetic shielding effectiveness. The electroless plating as an effective method for non-metallic surface metallizing satisfies the performances including good plating layer uniformity, corrosion resistance, abrasion resistance, electrical and magnetic properties [4][5][6]. The coating parameters directly affect the coating performance.…”
Section: Introductionmentioning
confidence: 99%